Pewarnaan bahan tekstil dengan menggunakan ekstrak kayu nangka dan teknik pewarnaannya untuk mendapatkan hasil yang optimal - Ainur Rosyida; Anik Zulfiya (Jurnal Rekayasa Proses, 2013)
This research aims to find a new plant that can be used as textile natural dye substance and the colour it produced. It also purposes to find coloration method of natural fabric by natural dye substance from jackfruit wood exstract to gain the optimum result.Dye solvent obtained by extracting jackfruit wood. Coloration system used exhaustion by jigger machine which included some steps namely : cotton fabric was impregnated into jackfruit wood extract in room temperature during 30 minutes, then electrolyte and coloration addition during 45 minutes. The next step was acid/base addition to get appropriate pH and coloration continued about 30 minutes in room temperature. Futhermore fabric was squeezed and fixated during 15 minutes in room temperature, the last step was fabric washing.Based on the research result, jackfruit wood extract can be used for coloring natural fibers (cotton fabric) of textile material into yellow and brown. Final result of coloring depends on fixator used but the color direction depends on pH used in coloration.The coloration method used shows that it gives optimum result because it produces smooth, permanent and dark colour as well. The result of faded tenacity caused by washing and incitement shows good value, it is 4-5. It proves that jackfruit wood extract can be used as fabric dye substance.